Affirmative action policies, people with disabilities and recognition of identities and differences in Brazilian higher education - Leonardo Santos Amâncio Cabral (Arizona State University, 2018)
The juridical and social recognition of differences and identities in the field of affirmative action policies aimed to promoting the access of people with disabilities to Brazilian Higher Education is an emerging in the national scenario. Thus, it is understood the need of discussions and theoretical, conceptual and juridical deepening that touches on the problematic. In this sense, the present research focused on the analysis of documents and studies on the subject in the spheres of political sciences, education, philosophy, sociology and cultural studies. As result, it weaved a national and international historical contextualization crossed by movements that culminated in the democratization of the access at the Higher Education, tied by problematizations about the material equality of rights, recognition of the difference and the plurality of identities, affirmative action policies, quota system and allusions to the possible interests and mechanisms of state regulations that govern in this process. It is pointed out that affirmative action policies, even though they are recognized as important, do not seem sufficient for the access and permanence of people with disabilities in Brazilian higher education, once the university culture must be willing re-signified itself in this process, building opportunities in which differences and plurality of identities are recognized.